Gastric Schwannoma Mimicking Gastrointestinal Stromal Tumor (GIST)—A Diagnostic Dilemma - Aneeqa Qureshi; Huzafa Ali; Husnain Abbas; Dipendra Adhikari; Huzaifa Saqib; Talha Rashid; Layba Ahmed; Ayesha Siddiqa; Fatima Anjum (JGH Open)
ABSTRACT Background Gastric schwannomas (GS) are rare benign neurogenic tumors that can mimic gastrointestinal stromal tumors (GISTs) due to overlapping clinical and radiological features, posing a significant diagnostic challenge. Case Presentation We present the case of a 67‐year‐old female with epigastric swelling, initially suspected to be a GIST based on contrast‐enhanced CT findings. However, an ultrasound‐guided true‐cut biopsy and immunohistochemistry confirmed the diagnosis of gastric schwannoma. The tumor was resected through a successful wedge resection, and the patient recovered well postoperatively. Conclusion This case underscores the importance of histopathological evaluation and immunohistochemistry in differentiating GS from GISTs, highlighting the need for a correct preoperative diagnosis to guide appropriate management. Gastric schwannomas are typically benign with minimal malignant potential, and surgery is the treatment of choice. Further studies are needed to explore their long‐term outcomes and prognostic factors.